Tree islands enhance biodiversity and functioning in oil palm landscapes - Zemp, Clara; Nathaly Guerrero-Ramirez; Fabian Brambach; Kevin Darras; Ingo Grass; Anton Potapov; Alexander Röll; Isabelle Arimond; Johannes Ballauff; Hermann Behling; Dirk Berkelmann; Siria Biagioni; et al. (My University, 2023)
In the United Nations Decade on Ecosystem Restoration1, large knowledge gaps persist on how to increase biodiversity and ecosystem functioning in cash crop-dominated tropical landscapes2. Here, we present findings from a large-scale, 5-year ecosystem restoration experiment in an oil palm landscape enriched with 52 tree islands, encompassing assessments of ten indicators of biodiversity and 19 indicators of ecosystem functioning. Overall, indicators of biodiversity and ecosystem functioning, as well as multidiversity and ecosystem multifunctionality, were higher in tree islands compared to conventionally managed oil palm. Larger tree islands led to larger gains in multidiversity through changes in vegetation structure. Furthermore, tree enrichment did not decrease landscape-scale oil palm yield. Our results demonstrate that enriching oil palm-dominated landscapes with tree islands is a promising ecological restoration strategy, yet should not replace the protection of remaining forests.